2011
DOI: 10.1007/s12253-011-9453-0
|View full text |Cite
|
Sign up to set email alerts
|

Periacinar Retraction Clefting and D2-40 Expression in Prostatic Adenocarcinoma

Abstract: Retraction clefting is known to appear in various types of tumors, but it has only recently been recognized as a specific histological phenomenon. Previously, it was considered merely a laboratory procedure artifact, but lately, there have been some assumptions that peritumoral retractions actually represent lymphatic spaces. In our study, we analyzed neoplastic glands in 52 specimens of prostatic adenocarcinoma. Immunohistochemical analysis was performed using D2-40 antibody, to highlight lymphatic endotheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…8 Therefore, immunohistochemical detection of D2-40 antibody is useful to differentiate actual lymph vessels and lymphatic invasion from periacinar retractions. 9…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, immunohistochemical detection of D2-40 antibody is useful to differentiate actual lymph vessels and lymphatic invasion from periacinar retractions. 9…”
Section: Introductionmentioning
confidence: 99%
“…Irie et al (6) proposed that retraction artifact around tumorous tissue actually represent lymph vessel compartments and their appearance connected with lymph vessels invasion in breast carcinoma. In order to investigate this hypothesis we analyzed relationship between retraction artifact and expression of immunohistochemical marker of lymph vessels D2-40 in prostatic carcinoma (71). Neoplastic glands were analysed in 25 paraffin sections from radical prostatectomy specimens with prostatic adenocarcinoma diagnosis.…”
Section: Possible Origin Of Retraction Artifact In Prostate Carcinomamentioning
confidence: 99%
“…Three established diagnostic criteria for prostatic adenocarcinoma are the infiltrative growth pattern, the absence of a basal cell layer, and the presence of macro nucleoli [ 1 ]. Periacinar retraction cleftings, also known as retraction artifacts, periacinar halos, or cleft-like spaces, play a significant role in supporting the histopathological diagnosis of prostatic adenocarcinoma [ 1 , 2 , 3 , 4 , 5 ]. These clefts manifest as neoplastic cells “pull away” from the surrounding stroma, creating halos around the acini.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the so called retraction artifacts are suggested to represent an early stage of lymphovascular invasion in breast carcinoma. Ulamec et al [ 4 ], utilizing the D2-40 antibody to highlight lymphatic endothelium to differentiate between authentic lymph vessels or lymphovascular invasion and periacinar retraction clefts, observed a significant reduction in the number of lymph vessels in prostatic adenocarcinoma compared to the adjacent nonneoplastic prostatic tissue. As a result, they concluded that retraction clefts should be regarded as a distinct entity in prostatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%